2008
DOI: 10.3102/0034654307313402
|View full text |Cite
|
Sign up to set email alerts
|

Inductive Reasoning: A Training Approach

Abstract: Researchers have examined inductive reasoning to identify different cognitive processes when participants deal with inductive problems. This article presents a prescriptive theory of inductive reasoning that identifies cognitive processing using a procedural strategy for making comparisons. It is hypothesized that training in the use of the procedural inductive reasoning strategy will improve cognitive functioning in terms of (a) increased fluid intelligence performance and (b) better academic learning of clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
175
2
27

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(223 citation statements)
references
References 65 publications
10
175
2
27
Order By: Relevance
“…In our study, there was not much similarity between training games and criterial tests, so we conclude that our participants improved their narrow cognitive abilities rather than just specific testing skills. However, the problem of task specificity in cognitive training must be taken seriously (see : Klauer & Phye, 2008;Stankov, 1986;Herrnstein, Nickerson, Desanchez, & Swets, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, there was not much similarity between training games and criterial tests, so we conclude that our participants improved their narrow cognitive abilities rather than just specific testing skills. However, the problem of task specificity in cognitive training must be taken seriously (see : Klauer & Phye, 2008;Stankov, 1986;Herrnstein, Nickerson, Desanchez, & Swets, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…We also attempted to determine whether fluid intelligence could be improved through attention training with limited engagement of executive functions. Attention, executive control, and working memory are closely related concepts (Friedman et al, 2006;Klauer & Phye, 2008;Shimamura, 2000;Unsworth & Engle, 2006). Hence, training effects are likely to be contaminated and misinterpreted.…”
mentioning
confidence: 99%
“…The training presented is based on Klauer's theory of inductive reasoning and the German "Cognitive training for children" program (Klauer, 1989a;Klauer & Phye, 2008). Klauer defined inductive reasoning as the discovery of regularities through the detection of similarities, dissimilarities, or a combination of both, with respect to attributes or relations to or between objects (Klauer, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The facilitative effect of cognitive training appears to impact the first two phases (problem identification and problem representation) of the problem solving process. A review of approximately 80 research studies (Klauer and Phye 2008) has demonstrated the effectiveness of teaching both discrimination and generalization processing when working with a large cross-section of students in varied settings.…”
Section: Rohrermentioning
confidence: 99%
“…In the studies reviewed by Klauer and Phye (2008), all followed a program format consisting of 12 training sessions over a 3-to 4-week period with a total of 120 problem solving episodes. Each training session consisted of 10 problems.…”
Section: Rohrermentioning
confidence: 99%